Implementation of high‐throughput non‐invasive prenatal testing for fetal RHD genotype testing in England: Results of a cross‐sectional survey of maternity units and expert interviews. Issue 4 (11th June 2020) - Ryczek, Edyta; White, Judith; Carolan‐Rees, Grace
Abstract: Background: Previously, routine antenatal anti‐D prophylaxis (RAADP) was administered to all RhD‐negative mothers to reduce the risk of sensitisation in the UK's National Health Service (NHS). If the baby is RhD‐negative, RAADP is not required. In 2016, the UK National Institute for Health and Care Excellence (NICE) recommended non‐invasive prenatal testing (NIPT) for fetal RHD genotype as a cost‐effective option to guide RAADP. Objectives: To evaluate the implementation of high‐throughput NIPT for fetal RHD genotype in maternity units in England by addressing research recommendations from the NICE. These were to reduce uncertainty around the resource use and cost of staff training, management of samples and results and record‐keeping, as well as resultant changes to antenatal or post‐partum care and performance of NIPT. Methods: A cross‐sectional survey was developed and sent to clinicians at 39 English NHS Trusts in May 2018. Qualitative interviews with seven individuals were conducted to explore missing or contraindicatory data. Qualitative findings were supplemented with NIPT test results (April 2017 to February 2019) from English hospitals. Results: Staff reported that training took up to 30 minutes. There were no extra costs associated with sample management or additional appointments. Extra time required for record‐keeping and management of test results was balanced later in the patient pathway. The antenatal pathway was not changed in the Trusts surveyed. The survey revealed that four post‐partum scenarios were being used within English NHS Trusts. The frequency of inconclusive NIPT results was 4.3%. Conclusion: NIPT for fetal RHD genotype can be implemented without consuming substantial extra resources through incorporation into an existing patient pathway.